Diarios gratuitos atrapados en la crisis: dos formatos diferentes y un destino incierto. - López García, X.; Bellón Rodríguez, A.; de Mateo Pérez, R. (Revista Latina de Comunicación Social, 2014)
Introduction. Free print newspapers, one of the main innovations in the communications market, are a paradigm of the crisis and the debate over the print and digital platforms. Method. The article explores, through content analysis, interviews and panels of experts, seven print and online free newspapers that were launched in Galicia in the last five years. Results. The landscape of free newspapers has changed markedly and their promoters have followed four different strategies: maintenance of print and digital formats; closure of the newspapers; integration of paid-for modalities; and survival in the digital platform. In addition, there are small local newspaper initiatives such as Lindeiros. Conclusions. It seems that the free press is still unsure about what is its preferred dissemination platform and that the proximity markets seem to be suitable spaces for this type of press. Moreover, it is unclear whether the free press will maintain a stable position in the communication market.